Cobalt(III)‐Catalyzed, DMSO‐Involved, and TFA‐Controlled Regioselective C−H Functionalization of Anilines with Alkynes for Specific Assembly of 3‐Arylquinolines. Issue 12 (18th April 2019) - Zhang, Peiquan; Yang, Yurong; Chen, Zhiyong; Xu, Zhang; Xu, Xuefeng; Zhou, Zhi; Yu, Xiyong; Yi, Wei
Abstract: Herein, a novel cobalt(III)‐catalyzed and TFA‐controlled [3+2+1] cyclization of diverse anilines and terminal alkynes has been realized by using DMSO as both the solvent and the C1 source, which led to the specific synthesis of privileged 3‐arylquinolines in one pot and regioselectively. Mechanistic investigations revealed that this versatile transformation might be initiated with a C−H activation process and with a 2‐vinylbenzenamine species as the active intermediate. Abstract :